Enhanced brightness and photostability of dye-sensitized Nd-doped rare earth nanocomposite for in vivo NIR-IIb vascular and orthotopic tumor imaging - Syue-Liang Lin; Shih-Po Su; Yuan-Zhen Yang; Cheng-Yu Chiang; Hsin-Yu Chi; Cheng Allen Chang; Tse-Ying Liu; Huihua Kenny Chiang (Journal of Nanobiotechnology)
Abstract Rare-earth doped nanoparticles (RENPs) have shown promise in biomedical imaging, particularly within the NIR-IIb region, due to their deep tissue penetration and minimal light scattering. However, challenges such as low extinction coefficients, narrow excitation spectra, and prone to quenching in aqueous environments limit their effectiveness. To overcome these obstacles, we developed a novel dye-sensitized, onion-like Nd-doped RENP nanocomposite to enhance NIR-IIb imaging performance. The onion-like Nd-RENP nanocomposite markedly enhances emission intensity at 1525 nm within the NIR-IIb range by reducing quenching and improving spectral overlap. The integration of an IR783-containing micellar layer further stabilizes the NIR dye, mitigating quenching and photobleaching. In vivo imaging studies demonstrated a 75-fold increase in luminance and a 9-fold improvement in photostability compared to free NIR dyes in aqueous solutions. Time-dependent in vivo studies confirmed the nanocomposite’s capability for prolonged imaging of vascular and tumor tissues, maintaining high-resolution images for over an hour. Additionally, the nanocomposite supported successful 3D imaging reconstruction of biological tissues. The dye-sensitized onion-like Nd-RENP nanocomposite presents a significant advancement in NIR-IIb imaging, providing enhanced brightness and photostability. Its ability to maintain clear and stable imaging over extended periods suggests potential applications in dynamic vascular and tumor-targeted imaging. This innovation holds promise for future biomedical imaging technologies, particularly in areas requiring high-resolution and long-duration monitoring. Graphical Abstract